Chemical Investigation Of The Simple Ascidian Phallusia Nigra Savigny, 1816 Of Tuticorin Coast By Gc-Ms - S. GOPALAKRISHNAN,; V. K. MEENAKSHI,; D. SHANMUGA PRIYA, (International Journal of Pharma and Bio Sciences, 2011)
Ascidians is a rich source of bioactive secondary metabolites. Phallusia nigra, a simple ascidian belonging to the family Ascidiidae found in plenty throughout the year along the Tuticorin coast of India. The methanolic extract of Phallusia nigra was subjected to GC-MS analysis to determine the possible bioactive components. The analysis revealed the presence of eleven chemical constituents of which the major are: Methyl 3-bromo-1-adamantaneacetate (24.65%), n-Hexadecanoic acid (24.45%), 11-Hexadecen-1-ol,(Z)- (17.64%) and 2,6-Dimethyl-6-trifluoroacetoxyoctane (9.82%).